Ferramentas administrativas para micro e pequenas empresas - Cassanego Junior, Paulo Vanderlei (2006)
During the last decades the organizations had faced a competition for markets that little were differentiated, therefore the consumers if they contented with what he was offered to them. Today the consumers possess more information on products and markets, "the world of the businesses passed for great transformation, where the customers wait products of high quality, greater functionality and low price" (BRIMSON 1996, p. 17). To follow these new demands, the companies are having that to rethink its visions and strategies, to become more flexible the floating demands of the market. For this, they need to be prepared for eventual modifications in its products or services, developing individual and organizational capacities, thus increasing the ability to identify and to solve problems, generating a solid basement for the taking of strategical, decisions for the survival of the companies (BORGES, 2000, p.1). Therefore, this work identified the administrative tools of management used by the Small Companies of Santa Maria-RS, and after it suggested tools of easy applicability, to assist in the taking of decisions.